Influence of Teeth Preparation Finishing on the Adaptation of Lithium Disilicate Crowns - Salamoni Sinhori, Bruna; Andrada, Mauro Amaral Caldeira de; Carpena Lopes, Guilherme; Monteiro Junior, Sylvio; Baratieri, Luiz Narciso (International Journal of Biomaterials, 2017)
The polishing step of teeth preparations for crowns is a step often performed, so that there is an increased time during the clinical procedure. The aim of this study is to evaluate the marginal and internal adaptation of all-ceramic CAD/CAM lithium disilicate crowns in polished preparations for crown and nonpolished preparations for crowns. For this purpose, 20 first molars were selected, which were divided into two groups (n=10) G1, teeth that received surface roughening similar to preparation without polishing, and G2 (control), polished preparations. After the preparations were completed the teeth were scanned (Cerec Bluecam, Sirona, Bensheim, Germany), and the crowns were designed and machined using CAD/CAM technology (Sirona, Bensheim, Germany). The adaptation of the pieces was evaluated using polyvinyl siloxane replicas and stereomicroscope photographs with 70x magnifications. The normality test indicated a nonnormal result, so a Man–Whitney nonparametric test was performed. One out of the 24 measured regions showed a statistically significant difference (p=0.0494). With this study it can be concluded that crowns fabricated by CAD/CAM technology performed on unpolished preparations are not influenced by the internal marginal adaptation and the ceramic part and are different from polished preparations.